Molecular Characterization and Expression Analysis of Intercellular Adhesion Molecule-1 (ICAM-1) Genes in Rainbow Trout (Oncorhynchus mykiss) in Response to Viral, Bacterial and Parasitic Challenge - Zhai, Xue; Kong, Wei-Guang; Cheng, Gao-Feng; Cao, Jia-Feng; Dong, Fen; Han, Guang-Kun; Song, Yan-Ling; Qin, Chuan-Jie; Xu, Zhen (Frontiers in Immunology, 2021)
The intercellular adhesion molecule-1 (ICAM-1) as known as CD54 is a transmembrane cell surface glycoprotein, which interacts with two integrins (i.e., LFA-1 and Mac-l) important for trans-endothelial migration of leukocytes. The level of ICAM-1 expression is up-regulated in response to some inflammatory stimulations, including pathogen infection and proinflammatory cytokines. Yet, to date, our knowledge regarding the functional role of ICAM-1 in teleost fish remains largely unknown. In this study, we cloned and characterized the sequence of ICAM-1 in rainbow trout (Oncorhynchus mykiss) for the first time, which exhibited that the molecular features of ICAM-1 in fishes were relatively conserved compared with human ICAM-1. The transcriptional level of ICAM-1 was detected in twelve different tissues, and we found high expression of this gene in the head kidney, spleen, gills, skin, nose and pharynx. Moreover, upon stimulation with infectious hematopoietic necrosis virus (IHNV), Flavobacterium columnare G4 (F. columnare), and Ichthyophthirius multifiliis (Ich) in rainbow trout, the morphological changes were observed in the skin and gills and enhanced expression of ICAM-1 mRNA was detected both in the systemic and mucosal tissues. These results indicate that ICAM-1 may be implicated in the mucosal immune responses to viral, bacterial and parasitic infections in teleost fish, meaning that ICAM-1 emerges as a master regulator of mucosal immune responses against pathogen infections in teleost fish.